Analisis Tingkat Minat Pemuda Dalam Beternak Sapi Potong Di Kecamatan Kayu Aro Kabupaten Kerinci - Fina Amelia; Bagus Pramusintho; Fatati Fatati (CV. SINAR HOWUHOWU, 2026)
This study aimed to determine the level of youth interest in beef cattle farming and to analyze the relationship between socio-economic characteristics and youth interest in beef cattle farming in Kayu Aro District, Kerinci Regency. The research was conducted from April to May 2025 using a survey method. The respondents consisted of 38 young beef cattle farmers aged 16–30 years, selected through a census approach. Data were collected through observation, interviews, and documentation. The data were analyzed descriptively using a Likert scale and inferentially using the Pearson Chi-Square test.The results showed that the level of youth interest in beef cattle farming was categorized as high, with an average score of 72.36%. The indicators of pleasure, attention, awareness, and willingness obtained scores of 71.57%, 72.76%, 70.39%, and 74.73%, respectively. The Pearson Chi-Square analysis indicated that education level (p = 0.049) and farming experience (p = 0.024) had significant relationships with youth interest in beef cattle farming, whereas livestock ownership (p = 0.432) showed no significant relationship. Education and farming experience were identified as important factors in enhancing youth participation in beef cattle farming.Keywords: youth interest; beef cattle farming; education; farming experience.